The economic burden of obesity in 4 south-eastern European countries associated with obesity-related co-morbidities - Athanasakis, Kostas; Bala, Cornelia; Kokkinos, Alexander; Simonyi, Gabor; Karoliová, Klaudia Hálová; Basse, Amaury; Bogdanovic, Miodrag; Kang, Malvin; Low, Kaywei; Gras, Adrien (BMC health services research, 2024)
OBJECTIVE: To provide an assessment of the cost burden of obesity across a spectrum of obesity-related comorbidities (ORCs) for four countries in South-Eastern Europe (SEE). METHODS: A micro-costing analysis from the public payer perspective was conducted to estimate direct healthcare costs associated with ten obesity-related comorbidities (ORCs) in Czech Republic, Greece, Hungary, and Romania. A survey was administered to obtain healthcare resource use and unit cost data. Cost estimates were validated by local steering committees which comprised at least one public sector clinician and a panel of independent industry experts. RESULTS: Chronic kidney disease and cardiovascular diseases were the costliest ORCs across all 4 countries, where annual cost burden per ORC exceeded 1,500 USD per patient per year. In general, costs were driven by the tertiary care resources allocated to address treatment-related adverse events, disease complications, and associated inpatient procedures. CONCLUSIONS: Our findings confirm that the high prevalence of obesity and its comorbidities result in substantial financial burden to all 4 SEE public payers. By quantifying the burden of obesity from a public healthcare perspective, our study aims to support policy efforts that promote health education and promotion in combating obesity in the region.
Keywords: podpora zdraví; Economic burden; Humans; osobní újma zaviněná nemocí; obezita; finanční stres; Obesity; Prevalence; Cost analysis; lidé; prevalence; Financial Stress; náklady na zdravotní péči; Health Promotion; Financial costs; Health Care Costs; Cost of Illness